A Critical Discourse Analysis: Christchurch Shootings Incident in Online Newspaper - Aljannati, Aljannati (Research Community for Critical Society and Environment, 2024)
This research is a Critical Discourse Analysis (CDA) study which explore how was the Christchurch shootings incident represented in The Jakarta Post (TJP) online newspaper. The study examined the linguistics aspects, discourse practice in the way they give the information to the society, and the socio-cultural that influence the news text. For the framework, this research used three stages of Three-Dimensional model from Norman Fairclough (2013) about Critical Discourse Analysis. Classification scheme, nominalizations, active and passive sentence, and modality are used in this research to examine the linguistic aspects. This research reveals that TJP had tendency to say that Christchurch incident was a terror. In the first stage, for the classification scheme, TJP mostly used the word attack as the incident’s name, used the word people as the victims and used the word gunman as the suspect. Then, in active and passive sentences, TJP mostly used passive sentence because TJP focused on the victims of the incident. In the second stage, in producing the text, journalist of TJP mostly used indirect quotation. Furthermore, TJP used online newspaper as their media to distribute the text and the target readers of TJP were Indonesia society. In the last stage, the research showed that there was influence from government toward the news text about Christchurch incident.